Los recursos audiovisuales y el aprendizaje de las Ciencias Naturales en el cuarto grado de la Escuela Particular “Timoteo”, período 2021-2022. - Arias Capa, Lady Fernanda (2022)
The research called audiovisual resources and learning of the Natural Sciences in the fourth grade of the Private School "Timoteo" has as a general objective to determine the influence of audiovisual resources on the learning process in the area of Natural Sciences of fourth grade students of the "Timoteo" private elementary school of the city of Loja, period 2021 - 2022, three specific objectives were set: first, to diagnose the learning of the subject of Natural Sciences of fourth grade students; second, to plan and execute a proposal with activities using audiovisual resources aimed at improving learning processes, and finally, to evaluate the impact of audiovisual resources on the learning of the Natural Sciences subject of fourth grade students Grade School Basic Education Particular "Timoteo". It had a qualitative-quantitative approach, descriptive type with a quasi-experimental design, the methods used were: scientific, descriptive, analytical, hermeneutic and statistical; the techniques used are observation and interview; the instruments were observation sheet, pre - test and post-test; to collect information the teacher was interviewed and a diagnostic evaluation was applied to students. It was possible to identify the shortcomings in the learning process of the different blocks of the subject of Natural Sciences; to contribute to the strengthening of the learning of this subject an alternative proposal called "Science, fun and action" was designed to improve the learning of Natural Sciences, which was developed through activities based on the use of audiovisual resources which were applied without any difficulty. Therefore, it is concluded that audiovisual resources constitute an effective didactic strategy to strengthen the teaching and learning process in the subject Natural Sciences. Keywords: audiovisual resources, teaching, learning, Natural Sciences, didactic strategy.